2015
DOI: 10.3402/gha.v8.23968
|View full text |Cite
|
Sign up to set email alerts
|

Engaging community health workers in maternal and newborn care in eastern Uganda

Abstract: BackgroundCommunity health workers (CHWs) have been employed in a number of low- and middle-income countries as part of primary health care strategies, but the packages vary across and even within countries. The experiences and motivations of a multipurpose CHW in providing maternal and newborn health have not been well described.ObjectiveThis study examined the perceptions of community members and experiences of CHWs around promoting maternal and newborn care practices, and the self-identified factors that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
78
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 19 publications
(16 reference statements)
13
78
1
1
Order By: Relevance
“…While this finding was not significant in Cambodia in multivariate analysis, there was a positive association in the univariate analysis. Our findings are supported by studies from various countries that have demonstrated that a key component to establishing this trust was ensuring male involvement in the woman's care [34,38]. In Uganda, this was most pronounced in terms of birth preparedness, as men still dominate economic power and related decision making in many households [34].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While this finding was not significant in Cambodia in multivariate analysis, there was a positive association in the univariate analysis. Our findings are supported by studies from various countries that have demonstrated that a key component to establishing this trust was ensuring male involvement in the woman's care [34,38]. In Uganda, this was most pronounced in terms of birth preparedness, as men still dominate economic power and related decision making in many households [34].…”
Section: Discussionsupporting
confidence: 77%
“…Despite the expansion of primary health care systems, CHW activities and service delivery varies greatly across and even within countries [22,34]. Location and frequency of CHW visits during the antenatal period and the number and content of counseling messages delivered can vary even with large-scale integrated CHW programs in place [22,35].…”
Section: Discussionmentioning
confidence: 99%
“…Uganda is implementing the Uganda Minimum Health Care Package which primarily aims at increasing awareness and promoting community participation in health care delivery and utilization through pro-moting health, preventing diseases and community health initiatives 4 . One of the ways of doing this is through the Village Health Teams (VHTs) strategy which also aims at providing the much needed health education.…”
Section: Introductionmentioning
confidence: 99%
“…The important lesson learnt for countries that introduce community health workers for improving health care is that previous contextual assessments and careful and tailored selection of their activities might be key to their success. 12,13 A 'one size fits all' approach might not be appropriate.…”
Section: Discussionmentioning
confidence: 99%